Writing morphophonology, reading lexical tone: Linguistic and experimental evidence in favour of morphographic spelling in Kabiye (Togo). Issue 2 (2nd July 2016) - Roberts, David; Walter, Stephen L
ABSTRACT: The shorter a word, the more likely it is to be lexically ambiguous. In the toneless standard orthography of Kabiye, a language of Togo, numerous monosyllabic heterophonic homographs (tonal minimal pairs) and homophonic homographs occur in the imperative and six associated conjugations. This paper presents the complete catalogue of these verbs, and then examines them in natural contexts. It goes on to propose a morphographic spelling in which elided root-final labial consonants are written as superscript silent letters to help the reader identify the lexeme. This spelling is tested against a diacritic tonographic alternative in an oral reading experiment. The results show that those who learnt the morphographic spelling gained more in reading accuracy than those who learnt the tonographic spelling.